Analysis Of The Effect Of One Phase Open Stator On The Performance And Temperature Of A Three Phase Induction Motor Cage Rotor - Christover Pasaribu (IHSA Institute, 2020)
Induction motors are alternating current motors that are most often used in the industrial world. Induction motors are used as pumps, compressors, fans, conveyors, and supporting other production propulsion equipment. The use of induction motors in industry is more profitable than DC motors or synchronous motors, one of the advantages is a strong and durable construction and easy maintenance and high efficiency. The problem of one of the open stator phases is one of the problems in the operation of an induction motor. Therefore, it is necessary to conduct a study in the form of analysis and research in the laboratory to see how the opening of one of the stator phases affects the performance and temperature rise of the induction motor. The test is carried out by overloading the induction motor by 0.5 Nm; 1.0 Nm; 1.5 Nm; 2.0 Nm; 2.5 Nm; 3.0 Nm. From the research conducted, it can be concluded that, among others, the opening of a single stator phase results in greater motor losses and an increase in motor temperature. Motor efficiency is better when the motor is in normal phase condition.